Causal Factors and Effect of Coaching Behavior of Branch Managers in Banking Business - Jivasitthikul, Jiamjit; chunin, Manop; Wongpinpech, Pinkanok (Rajapark Journal, 2022)
The purpose of this study was to investigate the validity of the causal relation model of coaching behavior in the banking business. The sample consisted of 663 branch managers within the banking business in Thailand, and they were selected by stratified random sampling from branch managers of banks listed in the Top 100 of banking on the Stock Exchange of Thailand. Data was collected through a questionnaire with five factors considered: emotional intelligence, transformational leadership, trust building, coaching behavior, and self-esteem. Those data were analyzed by utilizing a structural equation model (SEM). Results indicated that the structural model was consistent with empirical data. Results indicated that the structural model was consistent with empirical data by a percentage of 67.8, with the variances associated with coaching behavior explained by emotional intelligence, transformational leadership, and trust building. Specifically, transformational leaders had the strongest direct effect on the coaching behavior of branch managers by a percentage of 78.3. Results indicated that the structural model was consistent with empirical data by a percentage of 95.55, with the variances associated with self-esteem explained by emotional intelligence, transformational leadership, trust building, and coaching behavior.